Gaya Bicara dan Penggunaan Retoris Anies Baswedan pada Pidato Gugatan Sengketa Pemilu 2024 - Ilma, Anwar; Hindun, Hindun; Nailatunnajah, Nailatunnajah; Sabirin , Abu Bakar (GERAM, 2024)
Indonesia has just gone through a period of democracy, namely the election of the President and Vice President. Behind it all, there are questions about whether the democratic process that was held was a picture of the democratic values of freedom, struggle, and honesty. Paslon 01 and 03 as the applicants appealed the election results to the Constitutional Court (MK) allegedly with allegations of fraud that occurred, the applicant pairs complemented with evidence containing data and facts that could strengthen the argument at the trial. This study aims to look at the speaking style and rhetorical devices used by Anies Baswedan in his inaugural speech at the 2024 Election dispute lawsuit hearing. The results of this study found that there was a speaking style in the speech with 3 (three) data that aimed to invite the audience to the focus of the problem being discussed and in accordance with the situation that was happening.  While in the language style or the use of rhetorical devices, Anies Baswedan used 4 (four) types of language styles, namely metaphor, hyperbole, allegory and personification, among the four language styles used, metaphorical language style as the most frequently used language style by the speaker in the 2024 election dispute trial with a total of 20 data.